Analisis Kesalahan Siswa dalam Mengoneksikan Konsep Matematika pada Materi Pola Bilangan Kelas VIII MTs Dakwah Islamiyah Putra Nurul Hakim Kediri Tahun Ajaran 2018/2019 - Mushawwir Fikri; Arjudin Arjudin; Nurul Hikmah; Nani Kurniati (Griya Journal of Mathematics Education and Application, 2022)
Connecting mathematical concepts is one of the abilities that every student should have. Being able to connect between concepts or principles in mathematics can help students in solving every math problem. This study aims to describe the type of errors in connecting mathematical concepts to the number pattern material made by students and to find out the factors of the error made. The subject of this study was students of class VIII at MTs Dakwah Islamiyah Putra Nurul Hakim Kediri in academic year 2018/2019. The type of this research is qualitative research with descriptive approach. Students’ error data obtained from the results of students’ written test and interviews. The results showed that the students made errors in connecting the concepts of number pattern material such as: 1) Errors in connecting topics which is in number pattern material. 2) Errors in connecting topics of number pattern material with other mathematical materials. 3) Errors in connecting number pattern material with the real-life problems. In addition, the factors which cause students made these errors such as: students did not understand the facts in the questions, students did not understand the concept of number pattern, students did not master the principle of number pattern, students did not master in mathematical operations and students were not careful in answering questions.